PENGGUNAAN MEDIA BUKU ILUSTRASI UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN PADA SISWA KELAS II SD N 173127 SIMANAMPANG - Putra Bronson Tampubolon; Melisa Nur Asima Sidabutar; Salim Efendi (STKIP Subang, 2025)
This study aims to examine the effect of using illustrated books on improving early reading skills in second-grade students of SD Negeri 173127 Simanampang. This study used a quantitative approach with an experimental design in the form of a pretest-posttest. Before conducting the pretest-posttest, the researcher first conducted a trial of the instrument in a different school from the main research school. The results of the validity test showed that of the 25 items tested, 20 were declared valid, while the other 5 items were invalid. The reliability test produced a Cronbach's Alpha value of 0.849, which is above the threshold of 0.70, so the instrument was declared reliable. Based on the difficulty level test, the questions were categorized as easy. The research subjects consisted of 12 second-grade students of SD Negeri 173127 Simanampang. The analysis results showed that the use of illustrated books had a positive impact on students' early reading skills. The students' average pretest score of 63.33 increased to 84.58 in the posttest. Based on the results of the hypothesis test, a significance value (2-tailed) of 0.00 was obtained, which is smaller than the significance level of 0.05. Thus, it can be concluded that the use of illustrated book media significantly contributes to improving students' early reading skills, including aspects of reading fluency, word recognition, and understanding of reading content. In addition, this media is also effective in fostering reading interest and encouraging students' active involvement in the learning process. Therefore, the application of illustrated book media has been proven to have a positive influence on improving early reading skills in class II of SD Negeri 173127 Simanampang.